(Study on Green Tea Instant Processing with Kweni Fruit Flavor Extract (Mangifera odorata, Grift) Using Spray Drying) - Sudibyo, Agus; -, Setyajid; Sukiman, Maman (Balai Besar Industri Agro, 2010)
Study of green tea instant processing with flavor of kweni fruit (Mangifera odorata Grift) using spray drying has been conducted. The objectives of this research were to obtain green tea instant with flavor of kweni fruit as product diversification of green tea and observe the effect of addition of kweni fruit extracted and Arabic gum to maltodextrin ratio toward the quality of green tea instant product. they were twoÂ stages of this research, i.e. the previous study and finally the main study. The previous study were ; (1) chemical properties analysis from green tea and kweni fruit including water content, volatile reducing substance (VRS) value, ash content, tannin and catechin, and microorganism contamination in terms of total plate count and colifrom bacteriae; (2) Determination the best condition for green tea extraction and (3) Determination the optimal condition for kweni fruit extraction. Green tea of grade III was extracted using hot water in 90 derajat C during 5, 8 and 11 minutes with green tea and hot water ratio at 10 : 100, 15 :100 and 20 g : 100 ml; while kweni fruit was extracted using etanol 90% concentration during 15, 30, 45 minutes with kweni fruit to etanol ration at 100 : 100, 100 : 200 and 200 g : 100 ml). The main study were green tea processing and product quality evaluation including the yield, water content, VRS value, ash content, tannin content and solution ability and sensory analysis of green tea instant product using hedonic test. The result showed that the addition of flavor extract from kweni fruit in producing green tea instant has given significantly effect to theÂ value of yield, VRS and ash content; however Arabic gum has given signicantly effet to the VRS vale. Generally, organoleptic evaluation showed that panelis more like the taste, aroma and color of the product. The best green tea instant product wih flavor extracted from kweni fruit was obtained from A1B3 treatmnet (Arabic gum to maltodextrin ratio at 9 : 1 and kweni fruit extract concentration 20%) with the yield 7.64% water content 7.14, VRS 7.25 meq/g, ash content 8.72% , tannin conten 8.96% and salvation 89.47%.